2009
DOI: 10.1029/2008jc005083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atmospheric coastal jet off central Chile on sea surface temperature from satellite observations (2000–2007)

Abstract: [1] The coast of central Chile is characterized by intermittent low-level along-shore southerly wind periods, called coastal jets (CJs). In this study, we take advantage of long-term satellite data to document the CJs characteristics over 2000-2007 and investigate its impact on upwelling. The CJ structure has a core some 100 km from the shore and a cross-shore scale of $160 km, and it usually lasts for several days (3-10). Its period of occurrence ranges from weekly to a few months. On the basis of covariance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
67
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 63 publications
11
67
0
1
Order By: Relevance
“…This band coincides with the transitional band of low variance in the Chl-a annual cycle described above ( Figure 5) and it is associated with the position of the coastal-CTZ jet, where WSC is close to zero (~75°W). In turn, this coincides with the climatological location of the low-level wind jet, which is characteristic in the region between 30 and 38°S [45,47]. On the other hand, the annual variance in sea level and EKE were mostly constrained to the CTZ, in agreement with the results of [10].…”
Section: Annual Chl-a Variability and Its Association With Wind Forcisupporting
confidence: 85%
“…This band coincides with the transitional band of low variance in the Chl-a annual cycle described above ( Figure 5) and it is associated with the position of the coastal-CTZ jet, where WSC is close to zero (~75°W). In turn, this coincides with the climatological location of the low-level wind jet, which is characteristic in the region between 30 and 38°S [45,47]. On the other hand, the annual variance in sea level and EKE were mostly constrained to the CTZ, in agreement with the results of [10].…”
Section: Annual Chl-a Variability and Its Association With Wind Forcisupporting
confidence: 85%
“…Hypoxia may result in the occurrence of denitrification in the water column (Naqvi et al, 2000 and2009). It has been suggested that, in addition to denitrification, anaerobic ammonium oxidation (e.g.…”
Section: Figmentioning
confidence: 99%
“…For example, the world's largest natural hypoxic zone that develops seasonally over the Western Indian continental shelf appears to have intensified over the last three decades (Naqvi et al, 2000 and2009). Given the huge increase in fertilizer consumptions in South Asia, this region is expected to receive large amounts of anthropogenic nutrient loadings through land runoff and atmospheric deposition (Seitzinger et al, 2002;Duce et al, 2008).…”
Section: Figmentioning
confidence: 99%
“…Within central-northern Chile the area around 30 • S is characterized by the most intense upwelling favorable winds (Shaffer et al, 1999;Rutllant and Montecino, 2002). Additionally, local high-frequency forcing in the region is associated with atmospheric coastal jets with periods less than 25 days, which are related to synoptic dynamics of the mid-latitude pressure perturbations, in this case high pressures that migrate toward the east Rahn and Garreaud, 2013) and play a major role in coastal upwelling (Renault et al, 2009(Renault et al, , 2012Aguirre et al, 2012). All these features make the region a natural laboratory to explore the forcing mechanisms and describe the physical processes that modulate coastal upwelling.…”
mentioning
confidence: 99%